Back in Black - Foster, Lori 1958-; Copyright Paperback Collection (Library of Congress) (New York : Berkley Publishing Group, 2010)
Gillian Noode is hired to be the publicist and "handler" for Drew Black, the president of a growing sports business and a tactless big mouth with a reputation for causing trouble.
Includes excerpts from Mad, bad and blonde (p. [285]-297) and Something about you (p. [301]-308).
Keywords: Businessmen -- Fiction; Women public relations personnel -- Fiction; Love stories